Improving Savings and Health through Minor Conservation Measures in the Home - Randall A. Cantrell (EDIS)
Mechanical upgrades can increase the overall performance of a house by as much as 40%–50%, and the remaining 50%–60% inefficiency in the overall performance of a home is largely misunderstood. This 4-page fact sheet discusses ways to improve your home by making minor conservation measures. Written by Randall A. Cantrell and published by the UF Department of Family, Youth and Community Sciences, March 2012.